#64 : Developmental Elasticity and Self-Correction: How Much Can Human Embryos “Stretch”? - Yanhe Liu; Jay Natalwala; Vincent Chapple (Fertility & Reproduction, 2023)
Background and Aims: The recent clinical application of time-lapse videography has enabled detection of abnormal cleavage (ABNC) in in vitro cultured human embryos and the quantification of their developmental speed. However, growing evidence has highlighted the inter-laboratory transferability issue when involving morphokinetics measures for embryo selection, as different culture conditions and patient profiles are known to alter embryo morphokinetics. Having originally reported several ABNC phenomena, our recent birth outcome data also implied a potential self-correction mechanism in ABNC affected embryos. In this abstract, we review the most up-to-date evidence in this field and highlight the elastic nature of embryo development. Method: Literature review. Results: In this abstract, data from both our group and others are analyzed from 2 different aspects. First, we discuss both embryo and patient factors that have been shown to alter embryo morphokinetics. We also share evidence supporting the ability of embryos to be elastic in morphokinetics without losing the ability to implant. We therefore stress that caution ought to be taken when applying morphokinetics based embryo selection, especially when such models were developed using an external dataset. Secondly, we present the various impacts of ABNC when it occurs at different developmental stages and with different number of occasions. We also present the live birth rates and neonatal outcomes of ABNC embryos that had successfully achieved blastulation. Based on that, we propose blastulation as a self-correction milestone, supported by time-lapse footage showing exclusion/extrusion of ABNC-affected cells. Conclusion: Human embryos demonstrate detectable developmental elasticity which may be related to their ability to stand physical and chemical stress during in vitro culture. Embryos affected by ABNC can self-correct at blastulation by excluding/extruding affected cells. However, the limits of such elasticity in human embryos before losing their viability remain unknown.